2008
DOI: 10.1016/j.ijgo.2007.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a comprehensive university hospital-based infertility program in Nigeria

Abstract: Pregnancy outcome was relatively poor because conventional treatments did not cure the most prevalent causes of infertility, and assisted reproductive technology is therefore advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…Conventional infertility treatments are not always effective, however, as shown in a report from the University of Benin Teaching Hospital (UBTH) [6]. A study of the first 10 years of a 21-year infertility program at UBTH, implemented with the help of the WHO and in which only conventional methods were used, revealed that no pregnancies occurred for 60% of almost 2000 couples treated during these years.…”
Section: Introductionmentioning
confidence: 47%
See 1 more Smart Citation
“…Conventional infertility treatments are not always effective, however, as shown in a report from the University of Benin Teaching Hospital (UBTH) [6]. A study of the first 10 years of a 21-year infertility program at UBTH, implemented with the help of the WHO and in which only conventional methods were used, revealed that no pregnancies occurred for 60% of almost 2000 couples treated during these years.…”
Section: Introductionmentioning
confidence: 47%
“…Since the Unit was a WHO collaborating center in human reproduction, it was visited from time to time by resource persons from the WHO headquarters in Geneva. These persons supervised and streamlined the program during the 5 years of the LID grant duration and a report on the first 10 years of the experiment was published by Orhue et al [6]. The results revealed that, in spite of all the concerted efforts to treat their infertility, about 60% of the couples did not achieve pregnancy by the conventional methods practiced.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Nigeria found a cumulative incidence of pregnancy of 40% in 1948 couples followed up for a maximum of 10 years. 8 In Ghana, a cumulative incidence of spontaneous pregnancies of 12% was reported among 1000 infertile patients followed up for 18 months. 6 Rwanda is a poor, overpopulated and landlocked country in Central Africa and the Great Lakes region.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiological factors include tuboperitoneal diseases, anovulation, uterine lesions and semen fluid abnormalities (Adeyemi et al, 2009;Obuna et al, 2012;Orhue and Aziken, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Infertility, which refers to the inability of a couple to conceive after one year of regular unprotected sexual intercourse, is the commonest indication for outpatient gynaecological consultation in Nigeria (Adeyemi et al, 2009;Obuna et al, 2012;Orhue and Aziken, 2008;Ikechebelu, 2005;Karshima et al, 2014). The aetiological factors include tuboperitoneal diseases, anovulation, uterine lesions and semen fluid abnormalities (Adeyemi et al, 2009;Obuna et al, 2012;Orhue and Aziken, 2008).…”
Section: Introductionmentioning
confidence: 99%